1984
DOI: 10.1128/iai.43.2.523-530.1984
|View full text |Cite
|
Sign up to set email alerts
|

Role of cellular lipoteichoic acids in mediating adherence of serotype III strains of group B streptococci to human embryonic, fetal, and adult epithelial cells

Abstract: Lipoteichoic acids (LTA) of serotype III strains of group B streptococci (GBS) were shown to mediate adherence of these organisms to human embryonic (HEC), fetal (HFC), and adult buccal (HBEC) epithelial cells. The binding of GBS was temperature dependent, and maximum attachment occurred at 37°C. HEC, HFC, and HBEC preincubated with purified LTA significantly inhibited attachment of GBS, whereas the group B and type III antigens had no effect. Under phosphate-limiting conditions in which cell-associated LTA co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
2

Year Published

1985
1985
2010
2010

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(28 citation statements)
references
References 36 publications
3
23
2
Order By: Relevance
“…Age-related susceptibility to diseases caused by GAS has been suggested by the findings of Ofek et al (12), which demonstrated that LTA-mediated attachment of GAS to adult epithelial cells was 10-fold higher than that in neonatal cells. Conversely, Nealon and Mattingly (10) showed that GBS isolated from infected infants bound more avidly to human embryonic and fetal epithelial cells than to adult cells, and the specificity was attributable to long-chain molecules of LTA (11). The model for the participation of LTA in mediating attachment of GAS to epithelial cells requires the release of LTA from the cytoplasmic membrane and subsequent orientation at the cell surface with the fatty acid moieties available for interaction with hydrophobic domains on the surface of the epithelial cell (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age-related susceptibility to diseases caused by GAS has been suggested by the findings of Ofek et al (12), which demonstrated that LTA-mediated attachment of GAS to adult epithelial cells was 10-fold higher than that in neonatal cells. Conversely, Nealon and Mattingly (10) showed that GBS isolated from infected infants bound more avidly to human embryonic and fetal epithelial cells than to adult cells, and the specificity was attributable to long-chain molecules of LTA (11). The model for the participation of LTA in mediating attachment of GAS to epithelial cells requires the release of LTA from the cytoplasmic membrane and subsequent orientation at the cell surface with the fatty acid moieties available for interaction with hydrophobic domains on the surface of the epithelial cell (13).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that lipoteichoic acids (LTA) play a major role in the adherence of serotype III strains of group B streptococci (GBS) to human embryonic and fetal epithelial cells (10). An initial binding phase occurred within the first 10 min after the addition of bacteria and appeared to be hydrophobic in nature (11).…”
mentioning
confidence: 99%
“…However, 100% inhibition with the antiserum was not achieved, suggesting that there are additional interactions between GBS and U937 cells. This is supported by work of Nealson and Mattingly [7] who showed that puri¢ed LTA was able to signi¢cantly inhibit adherence of GBS to embryonic cells. Because 100% inhibition could not be achieved, they suggested that attachment is most likely a multi-step process and that other receptors are involved.…”
Section: Discussionmentioning
confidence: 53%
“…Investigations of lipoteichoic acid (LTA) and adherence are contradictory. Several reports implicated LTA in adherence by showing that preincubation of epithelial cells with soluble LTA at high concentrations inhibited attachment of GBS (20). Others, however, who employed similar concentrations of LTA, did not observe an inhibitory effect (1).…”
Section: Discussionmentioning
confidence: 99%